Equilibrium in a Market with Sequential Bargaining - Rubinstein, Ariel; Wolinsky, Asher (Econometrica, 1985)
This paper considers a market where pairs of agents who are interested in carrying out a transaction are brought together by a stochastic process and, upon meeting, initiate a bargaining process over the terms of the transaction.The basic bargaining problem is treated with the strategic approach.The paper derives the steady state equilibrium agreements; analyzes their dependence on market conditions such as the relative numbers of agents of different types; and discusses their relations with the competitive equilibrium outcome and other results in the search equilibrium literature.1133